NURSING ROLE IN BREAST CANCER AWARENESS AND SCREENING - Wafaa Sayah Maqbul Alsharari, Abeer Abdullah Almabruk, Tharwah Mohammed Jawban Alruwaili, Atlal Adel Algader, Naseem Salem Shaman, Munirah Awad Oshban Alanazi (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Breast cancer is one of the most serious health challenges affecting women across the world. Early awareness and screening are critical in improving health outcomes and patient survival. Nurses are central figures in health education, patient counseling, and community engagement. Their involvement in awareness programs and screening campaigns enhances women’s understanding of risk factors, self-examination practices, and the importance of timely medical evaluation. This paper explores the essential role of nurses in breast cancer awareness and screening, emphasizing education, communication, empathy, and collaboration with multidisciplinary teams.